Oral myiasis in a child with learning difficulties. - Akhtar, M.U.; Ali, K. (European Journal of Pediatric Dermatology, 2014)
We present an unusual case of oral myiasis in an 11-year old child with a history of learning difficulties since birth. The patient sustained an injury to her upper anterior teeth due to a fall at home and presented after five days with swelling and discomfort in her upper jaw. The clinical examination showed marked swelling associated with the gingival soft tissues of the upper incisor teeth. The wound was explored under local anaesthesia and revealed infestation of approximately 12 larvae. Following surgical debridement primary closure of the wound was obtained and the postoperative healing was uneventful. This case highlights a rare presentation of oral myiasis caused by Crysomya bezziana (Old World Screw worm) in a child with learning difficulties.